2017
DOI: 10.1177/1479164117698918
|View full text |Cite
|
Sign up to set email alerts
|

An additional bolus of rapid-acting insulin to normalise postprandial cardiovascular risk factors following a high-carbohydrate high-fat meal in patients with type 1 diabetes: A randomised controlled trial

Abstract: Aim:To evaluate an additional rapid-acting insulin bolus on postprandial lipaemia, inflammation and pro-coagulation following high-carbohydrate high-fat feeding in people with type 1 diabetes. Methods: A total of 10 males with type 1 diabetes [HbA 1c 52.5 ± 5.9 mmol/mol (7.0% ± 0.5%)] underwent three conditions: (1) a low-fat (LF) meal with normal bolus insulin, (2), a high-fat (HF) meal with normal bolus insulin and (3) a high-fat meal with normal bolus insulin with an additional 30% insulin bolus administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Sample size for this study was estimated on the basis of prior work in T1D with shared similarities as well as published meal tolerance data [24][25][26]. Priori power calculations estimated a sample size of n = 16 in each arm would provide 80% power with α set at 0.05 to detect a small effect (d = 0.25) in the change variables for primary and secondary outcomes, namely: VCAM-1, E selectin, P-selectin, TNFα, pentraxin-3, ICAM-1, VEGF, HbA1c, triglycerides, PPGR, and PPGT [27].…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…Sample size for this study was estimated on the basis of prior work in T1D with shared similarities as well as published meal tolerance data [24][25][26]. Priori power calculations estimated a sample size of n = 16 in each arm would provide 80% power with α set at 0.05 to detect a small effect (d = 0.25) in the change variables for primary and secondary outcomes, namely: VCAM-1, E selectin, P-selectin, TNFα, pentraxin-3, ICAM-1, VEGF, HbA1c, triglycerides, PPGR, and PPGT [27].…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…A good understanding of meal content and the glycaemic index is probably important for pump users to fully benefit from the effect of faster aspart. Although the use of faster aspart in the context of high‐ or low‐glycaemic index meals has not been addressed in clinical trials, there may be a need for different bolus types, such as a delayed/extended bolus with larger meals or a dual‐ or multi‐wave bolus for high‐fat and high‐protein meals (Figure ) . As a starting point for high‐fat and high‐protein meals, 30% of the total insulin dose can be administered immediately and 70% administered with a delay over the 2–4 hours following the meal.…”
Section: Faster Aspart Via Csii: Practical Considerationsmentioning
confidence: 99%
“…Although the use of faster aspart in the context of highor low-glycaemic index meals has not been addressed in clinical trials, there may be a need for different bolus types, such as a delayed/extended bolus with larger meals or a dual-or multi-wave bolus for high-fat and high-protein meals (Figure 2). [47][48][49] As a starting point for high-fat and high-protein meals, 30% of the total insulin dose can be administered immediately and 70% administered with a delay over the 2-4 hours following the meal. It should also be noted that more insulin than that calculated by carbohydrate counting alone may be needed.…”
Section: Faster Aspart Via Csii: Practical Considerationsmentioning
confidence: 99%
“…From the new insights about the effect of dietary macronutrients on post-prandial glucose control, it appears that, to improve the calculation of the insulin bolus, CC should be integrated with the counts of fats and proteins. On the other hand, it has been demonstrated that bolus calculation for high fat feeding prevents late rises in postprandial triglycerides and tumour necrosis factor alpha, thus improving cardiovascular risk profile [ 73 ]. Therefore, the development of suitable and usable algorithms is necessary, without forgetting the importance of educational therapy for a successful translation of fat/protein counting in real life [ 74 ].…”
Section: Insulin-to-carb Ratio (Icr) Insulin Sensitivity Factor (mentioning
confidence: 99%